2016
DOI: 10.2131/jts.41.479
|View full text |Cite
|
Sign up to set email alerts
|

Demethylation of methylmercury and the enhanced production of formaldehyde in mouse liver

Abstract: -Methylmercury (MeHg) is gradually changed to inorganic Hg after demethylation in animal tissues, and a selective quantification of inorganic Hg in the tissues is necessary to detect the reaction. We detected inorganic Hg formation in liver and kidney of mouse as early as 24 hr after MeHg injection. As an example of biological demethylation, the cytochrome P450 (P450)-mediated N-demethylation of drugs has been well documented, and formaldehyde was detected as a reaction product. Here we incubated mouse liver h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…These results suggest that a slow rate demethylation occurs in brain [71]. Toxicokinetic studies in human subjects suggest a positive correlation between the rate of MeHg demethylation into inorganic Hg and MeHg elimination rate [68]. Regarding excretion pathways, inorganic Hg can be excreted via bile discharges or via urine, while excretion of MeHg occurs predominantly via feces.…”
Section: Metabolism and Excretionmentioning
confidence: 89%
See 2 more Smart Citations
“…These results suggest that a slow rate demethylation occurs in brain [71]. Toxicokinetic studies in human subjects suggest a positive correlation between the rate of MeHg demethylation into inorganic Hg and MeHg elimination rate [68]. Regarding excretion pathways, inorganic Hg can be excreted via bile discharges or via urine, while excretion of MeHg occurs predominantly via feces.…”
Section: Metabolism and Excretionmentioning
confidence: 89%
“…In several organs, a small fraction of MeHg is gradually demethylated to inorganic mercury. In vitro studies have reported a dose-response relationship between MeHg administration and inorganic mercury accumulation [67,68]. Thus, even though MeHg-contaminated food constitutes the source of exposure, it is frequent to find both organic and inorganic mercurial species within the organism.…”
Section: Absorption and Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that FA can rapidly accumulate in organism, and is primarily associated with FA pollutants, [104,209] diets (deep‐sea fish polluted with methyl mercury [210,211] ), viral infect, [212–216] external stimuli, [19] stress, [20,36] and trauma, as well as with endogenous factors, such as: age, [11,32] stroke, [36] diabetes, [217] postoperative cognitive dysfunction (POCD), [218] and ALDH2 polymorphisms [217,219,210] (Figure 5a). The most direct evidence is that injection of 0.45 mM FA (a concentration detected in aged rats with cognitive deficits) can mimic memory disorders in healthy adult male mice and rats [10] …”
Section: New Drug For Targeting Aβ Dimersmentioning
confidence: 99%
“…Early embryogenesis is one of the most sensitive life stages to environmental toxicants, and while the developing brain is particularly sensitive to mercury toxicity (Hassan et al, 2012;Chan et al, 2017), other developing organ systems and tissues also are highly susceptible to mercury toxicity. Mechanisms through which mercury affects cellular functions include induction of apoptosis, increased cellular oxidative stress, reduced function of ion channels and neurotransmitter receptors, and perturbations in energy metabolism and calcium balance, primarily through effects on mitochondrial function and integrity are adversely affected when exposed to mercury (Reis et al, 2007;Uchikawa et al, 2016). Mercury also has a pronounced affinity for protein sulfhydryl (SH) groups that, when bound to mercury, will diminish or completely inhibit normal protein function, including enzyme functions (Reis et al).…”
Section: Introductionmentioning
confidence: 99%